Absence of Four-and-a-Half LIM Domain Protein 2 Decreases Atherosclerosis in ApoE−/− Mice. Issue 5 (May 2015) - Ebrahimian, Talin; Simon, David; Lemarié, Catherine A.; Simeone, Stefania; Heidari, Maryam; Mann, Koren K.; Wassmann, Sven; Lehoux, Stephanie
<x xml:space="preserve">Abstract</x> Objective— Four-and-a-half LIM domain protein-2 (FHL2) is expressed in endothelial cells, vascular smooth muscle cells, and leukocytes. It regulates cell survival, migration, and inflammatory response, but its role in atherogenesis is unknown. Approach and Results— To investigate the role of FHL2 in atherosclerosis, FHL2-deficient mice were crossed with ApoE-deficient mice, to generate ApoE/FHL2−/− mice. After high-fat diet, ApoE/FHL2−/− mice had significantly smaller atherosclerotic plaques than ApoE−/− mice in the aortic sinus, the brachiocephalic artery, and the aorta. This was associated with enhanced collagen and smooth muscle cell contents and a 2-fold reduction in macrophage content within the plaques of ApoE/FHL-2−/− versus ApoE−/− mice. This could be explained, in part, by the reduction in aortic ICAM-1 (intracellular adhesion molecule) mRNA and VCAM-1 (vascular cell adhesion molecule) protein expression in the plaque. Aortic gene expression of the chemokines CX3CL1 and CCL5 was increased in ApoE/FHL2−/− versus ApoE−/− mice. Peritoneal thioglycollate injection elicited equivalent numbers of monocytes and macrophages in both groups, but a significantly lower number of proinflammatory Ly6C high monocytes were recruited in ApoE/FHL2−/− versus ApoE−/− mice. Furthermore, mRNA levels of CX3CR1 were 2-fold higher in monocytes from ApoE/FHL2−/− versus ApoE−/− mice. Finally, we investigated the potential importance of myeloid cell FHL2 deficiency in atherosclerosis. After being irradiated, ApoE−/− or ApoE/FHL2−/− mice were transplanted with ApoE−/− or ApoE/FHL2−/− bone marrow. After high-fat diet, both chimeric groups developed smaller plaques than ApoE−/− transplanted with ApoE−/− bone marrow. Conclusions— These results suggest that FHL2 in both myeloid and vascular cells may play an important role in atherosclerosis by promoting proinflammatory chemokine production, adhesion molecule expression, and proinflammatory monocyte recruitment.